2015
DOI: 10.1016/j.jadohealth.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity, Sexual Orientation, and Eating-Related Pathology in a National Sample of College Students

Abstract: Purpose This study examined associations of gender identity and sexual orientation with self-reported eating disorder (SR-ED) diagnosis and compensatory behaviors (CB) in trans- and cis-gender college students. Methods Data came from 289,024 students from 223 U.S. universities participating in The American College Health Association – National College Health Assessment II (median age 20 years). Rates of self-reported past year SR-ED diagnosis and past month use of diet pills and vomiting or laxatives were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
269
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(295 citation statements)
references
References 37 publications
(60 reference statements)
21
269
2
3
Order By: Relevance
“…2009, Centers for Disease Control and Prevention 2011, Austin et al . 2012, Diemer et al . 2015, Laska et al .…”
Section: Introductionmentioning
confidence: 99%
“…2009, Centers for Disease Control and Prevention 2011, Austin et al . 2012, Diemer et al . 2015, Laska et al .…”
Section: Introductionmentioning
confidence: 99%
“…Past research on disordered weight control has focused almost exclusively on cisgender women (Smink et al, 2012; Thompson, 1999); only a few recent studies have focused on transgender individuals (Ålgars et al, 2012; Diemer et al, 2015; Witcomb et al, 2015). This study found that 16 of 21 participants reported some level of disordered weight and shape control.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, preliminary evidence for eating disorders risk in transgender populations is troubling: in a study of 280,000 U.S. college students, transgender students had two times greater odds of a past-year diagnosis of anorexia nervosa or bulimia nervosa compared to cisgender heterosexual women (Diemer et al, 2015). Very little research has focused on transgender women, who may have distinct risk profiles (Ålgars et al, 2012; Vocks et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lesbians are more likely to be overweight than heterosexual teenage girls, with binge eating being a significant risk factor 13. Transgender teenagers are four times more likely than cisgender (non-trans) peers to have an eating disorder,14 and management is complicated as diet can be related to attempts to control development of unwanted secondary sex characteristics (eg, fat deposition patterns and menstruation).…”
Section: Public Health and Preventionmentioning
confidence: 99%